2015
DOI: 10.1556/eujmi-d-15-00001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nasal colonization with β-lactamase-producing enterobacteriaceae in patients, health care workers and students in Madagascar

Abstract: This study assesses the nasal occurrence of β-lactamase-producing Enterobacteriaceae both in patients in a hospital department of infectious diseases at admission and in healthy Madagascan students and health care workers.Nasal swabs from 681 students, 824 health care workers, and 169 patients were obtained in Antananarivo, Madagascar, and transferred to Germany. Screening for β-lactamase (ESBL, ampC) producing Enterobacteriaceae was performed by cultural and molecular approaches, comprising Brilliance ESBL ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Considering the fact that colonization frequently precedes infection, the observation by Yun et al [ 25 ] that local forces in Iraq showed high colonization rates of skin and mucous membranes with Gram-negative bacteria is of particular importance. Similar data on Gram-negative colonization of skin and mucous membranes with Gram-negative Enterobacteriaceae were recently described for patients, students, and healthcare workers in the highlands of Madagascar [ 72 ]. The reasons are unclear, although high temperatures and humidity which are frequent in subtropical and tropical settings were described to facilitate Gram-negative bacterial growth on human skin [ 73 ].…”
Section: Discussionsupporting
confidence: 75%
“…Considering the fact that colonization frequently precedes infection, the observation by Yun et al [ 25 ] that local forces in Iraq showed high colonization rates of skin and mucous membranes with Gram-negative bacteria is of particular importance. Similar data on Gram-negative colonization of skin and mucous membranes with Gram-negative Enterobacteriaceae were recently described for patients, students, and healthcare workers in the highlands of Madagascar [ 72 ]. The reasons are unclear, although high temperatures and humidity which are frequent in subtropical and tropical settings were described to facilitate Gram-negative bacterial growth on human skin [ 73 ].…”
Section: Discussionsupporting
confidence: 75%
“…One reason is the fact that there are numerous different molecular mechanisms, exceeding the potentials even of multiplex PCR approaches. However, if only singular or few resistance determinants circulate within a local population as suggested for Mali, PCR-based screening might be successfully applied as recently demonstrated for a setting in Madagascar [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inhabitants of tropical or subtropical climate zones were shown to have high colonization rates of skin and mucous membranes with Gram-negative rod-shaped bacteria [21]. High frequencies were also reported from patients, students, and health-care workers in Madagascar [22]. This makes the discrimination between wound colonization and wound infection challenging.…”
Section: Plos Onementioning
confidence: 99%